Neutrophil Activity Depending On Microorganism Resistance To Antibacterial Therapy In Sepsis Patients - Khayitov D. H (Genius Journals, 2024)
Sepsis has been and continues to be the most frequent cause of mortality in intensive care units. Despite modern methods of diagnosis and treatment, high mortality in sepsis patients remains a worldwide problem. One important aspect in the management of sepsis is antibiotic therapy, but the efficacy of this treatment can be severely compromised by resistance of microorganisms to the antibiotics used. Neutrophils, key cells of the immune system, play a crucial role in fighting infection. However, how neutrophil levels and activity are altered by microbial resistance to antibiotic therapy in patients with sepsis remains a subject of active research.
Keywords: antibiotic-resistant microorganisms; leukocyte sensitivity; neutrophil traps